Thymoglobulin Induction Dosing Strategies in a Low-Risk Kidney Transplant Population: Three or Four Days? - Karen L. Hardinger; Rafia S. Rasu; Rebecca Skelton; Brent W. Miller; Daniel C. Brennan (Journal of Transplantation)
The optimal dose and duration of rabbit antithymocyte globulin (rATG) induction has not been defined. Methods. We compared the safety and efficacy of 2 dosing strategies, rATG 1.5 mg/kg for 4 days (n=59) versus 2 mg/kg for 3 days (n=59), in a retrospective, cohort study. Results. Two-year rejection-free survival was 95% in each group (P=.983). Renal function and infection rates were similar. The incidence of leucopenia was similar, although the 2 mg/kg group was more likely to be thrombocytopenic on day 2 (4% versus 28%, P=.04). Length of stay tended to be longer for the 1.5 mg/kg group (6.0±3.7 versus 5.1±1.9 days P=.104). A cost savings of $920 per patient for rATG were seen in the 2 mg/kg group (P=.122). Conclusions. Shorter, more intense dosing of rATG is safe and effective. The 3-day dose strategy resulted in a clinically shorter length of stay and may result in cost savings.